Can Watching a Television Documentary Change the Way Men View Masculinity?. Issue 3 (October 2019) - King, Kylie; Schlichthorst, Marisa; Keogh, Louise; Reifels, Lennart; Spittal, Matthew J.; Phelps, Andrea; Pirkis, Jane
Men's conformity to masculine norms, such as stoicism and self-reliance, has been shown to be associated with a range of negative psychological outcomes. We developed Man Up —a three-part documentary that examined the link between masculinity, mental health, and suicide for men in Australia. We conducted a multifaceted evaluation that included a randomized controlled trial (RCT) and a web survey. RCT participants and web survey respondents were asked how their views of the term "man up" had changed since watching the documentary. This article provides feedback from the 306 men who responded to this question. Participants commented on how the documentary prompted them to rethink stereotypes of masculinity. The findings suggest that the documentary had a positive impact on men.